A broken chain? Colonial history, middle-class Indian migrants and intergenerational ambivalence. (February 2019) - Gallo, Ester
The article explores ambivalence among middle-class Indian migrants who return to India after their retirement. It discusses intergenerational ambivalence from the dual perspectives of the relation between older migrants and their parents, and that linking the former to their migrant children today. Older migrants' transnationalism is an important yet under-researched topic. It offers insights into the temporal dimension of ambivalence: how family contradictions accompany and change throughout the life course, and how they orient migrants' understandings of the past, present, and future. Central to the analysis is the relation between migrant intergenerational ambivalence and the historical development of the Malayali middle class at home and in the diaspora. Moving beyond studies on ambivalence that mainly focus on Euro-American societies, it explores the phenomenon in postcolonial locations. The article discusses the extent to which colonial forms of socio-geographical mobility shape older migrants' ambivalence across generations, vis-á-vis broader middle-class expectations around educational/professional attainment, reproductive choices, and care provision. It suggests that a temporal perspective on ambivalence is useful to highlight how transnational family ambivalence is shaped not only by present-day uncertainties but also by political and cultural history. It also enhances our understanding of how dispersed families negotiate ambivalence in the long term, and the cumulative effects of these negotiations in the production of novel care arrangements in the present.